(B, N)-Doped 3D porous graphene–CNTs synthesized by chemical vapor deposition as a bi-functional catalyst for ORR and HER. Issue 47 (30th July 2018) - Gao, Pingping; Sun, Min; Wu, Xiaobo; Zhou, Shuzhu; Deng, Xiaoting; Xie, Zhiyong; Xiao, Li; Jiang, Lihui; Huang, Qizhong
Abstract : A simple but very efficient two-step CVD method to prepare a (B, N)-doped 3D porous graphene–CNT hybrid material (B–N–G–CNT), and its catalytic performance for ORR and HER. Abstract : Novel (B, N)-doped three-dimensional (3D) porous graphene–carbon nanotubes (CNTs) can be used as an excellent alkaline and acid tolerant electrocatalyst for both the oxygen reduction reaction (ORR) and the hydrogen evolution reaction (HER). Based on density functional theory, the H and O atoms' pre-and post-adsorption energy can effectively reduce the reaction energy barrier.